2019
DOI: 10.1111/tpj.14179
|View full text |Cite
|
Sign up to set email alerts
|

Computational aspects underlying genome to phenome analysis in plants

Abstract: Summary Recent advances in genomics technologies have greatly accelerated the progress in both fundamental plant science and applied breeding research. Concurrently, high‐throughput plant phenotyping is becoming widely adopted in the plant community, promising to alleviate the phenotypic bottleneck. While these technological breakthroughs are significantly accelerating quantitative trait locus (QTL) and causal gene identification, challenges to enable even more sophisticated analyses remain. In particular, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 180 publications
(202 reference statements)
0
35
0
Order By: Relevance
“…In this issue, Bolger et al . () argue for the relevance of GxE in understanding phenotypic traits. They discuss how understanding this phenomenon is fundamental for QTL and GWA studies.…”
mentioning
confidence: 99%
“…In this issue, Bolger et al . () argue for the relevance of GxE in understanding phenotypic traits. They discuss how understanding this phenomenon is fundamental for QTL and GWA studies.…”
mentioning
confidence: 99%
“…The last few years have seen a tremendous advance in plant genomic sciences driven by technologies such as long read PacBio and lately Oxford Nanopore sequencing (Bolger et al , 2019) as well as new technologies to obtain long range structural information such as optical mapping and Hi-C based information (Schreiber, Stein and Mascher, 2018) . Indeed, it has been shown that these technological advances can be used to get (near) chromosome scale assemblies of sub-Gigabase genomes (Belser et al , 2018) and that they are particularly useful to unravel the genomes of wild species which are close relatives of important crops providing information about exotic germplasm and its use (Wu et al , 2018) .…”
Section: Discussionmentioning
confidence: 99%
“…This affordability and simplicity has enabled the rapid uptake of MinION sequencing by individual labs worldwide and facilitated new applications such as the rapid on-field detection of Cassava mosaic begomoviruses in Sub-Saharan Africa [74] or the assembly of highly contiguous genome of A. brassicae [75] in India. Despite the rapid evolution and constant improvement of next generation sequencing technologies, many standard pipelines and tools that can potentially assemble a reasonable quality genome are available for both sequencing technologies [76]. What is required is for the user to have an acceptable level of familiarity with the technology, the data and the genome to be assembled.…”
Section: Computational Resources On Plant Genomicsmentioning
confidence: 99%